CLivD score modifies FIB-4 performance in liver fibrosis detection in the US general population - Mitja Lääperi; Fredrik Åberg; Ville Männistö (eGastroenterology)
Background and aims Steatotic liver disease (SLD) is a growing global concern. The Chronic Liver Disease (CLivD) risk score predicts liver-related outcomes in the general population using easily accessible variables with or without laboratory tests (CLivDlab and CLivDnon-lab). We assessed CLivD’s associations with liver steatosis, fibrosis and its combined performance with fibrosis-4 (FIB-4) for advanced fibrosis detection.Methods Using the National Health and Nutrition Examination Survey data (2017–2020), 3603 participants aged 40–70 years with valid liver stiffness measurements (LSMs) were included. Advanced fibrosis was defined as LSM ≥12 kPa, and SLD as controlled attenuation parameter ≥288 dB/m.Results Significant associations were found between CLivD and SLD and advanced fibrosis. CLivDlab had an area under the curve (AUC) for advanced fibrosis of 0.72 (95% CI 0.68 to 0.77), while CLivDnon-lab had an AUC of 0.68 (95% CI 0.64 to 0.72), both slightly higher than FIB-4 (AUC 0.66, 95% CI 0.60 to 0.72). Among participants without obesity, AUC of CLivDlab was 0.82 (95% CI 0.76 to 0.88) and AUC of CLivDnon-lab was 0.72 (95% CI 0.65 to 0.79). The CLivD score improved FIB-4’s AUC for advanced fibrosis detection from <0.5 at minimal CLivD scores to >0.8 at high CLivD scores. A sequential CLivD→FIB-4 strategy outperformed universal FIB-4 testing, enhancing specificity from 72% to 83%, with sensitivity at 51%–53%. This strategy identified a subgroup with a 55% prevalence of advanced fibrosis, while 47% had minimal-risk CLivD scores, eliminating the need for FIB-4 testing.Conclusions The CLivD score, designed for predicting liver-related outcomes, effectively identifies liver steatosis and advanced fibrosis in the general population. Combining CLivD with FIB-4 enhances advanced fibrosis detection accuracy. The CLivD score could enhance population-based liver fibrosis screening, optimising resource allocation.